2021
DOI: 10.18488/journal.61.2021.92.323.339
|View full text |Cite
|
Sign up to set email alerts
|

Developing Virtual Communication Skills in Online Learning Based on Modified PBL During the Covid-19 Pandemic

Abstract: This study aims to determine the virtual communication skills of students in the Vertebrate Zoology course, the subject of the Reptile Class with the example of the Varanus salvator species. The research was conducted by survey method using an adaptation observation sheet from the 2012 Greenstein instrument. Data collection was carried out on modified online Problem Based Learning (PBL) using Zoom meeting and WhatsApp Group (WAG). While presentation and organizing stages were carried out by class discussion on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
(24 reference statements)
0
13
0
5
Order By: Relevance
“…It is also a common phenomenon in various institutions and countries. Some research results related to the use of WhatsApp can corroborate this (Ahmed, 2019;Balcı & Kartal, 2021;Enyama et al, 2021;Hikamah et al, 2021;Madge et al, 2019;Ritonga et al, 2020;Robles et al, 2019;Suhaimi et al, 2019). Among the considerations is choosing one that is simple, easy to use, and familiar.…”
Section: Introductionmentioning
confidence: 76%
“…It is also a common phenomenon in various institutions and countries. Some research results related to the use of WhatsApp can corroborate this (Ahmed, 2019;Balcı & Kartal, 2021;Enyama et al, 2021;Hikamah et al, 2021;Madge et al, 2019;Ritonga et al, 2020;Robles et al, 2019;Suhaimi et al, 2019). Among the considerations is choosing one that is simple, easy to use, and familiar.…”
Section: Introductionmentioning
confidence: 76%
“…Communication occurred exclusively electronic, virtual, and remote, with the use of technology, being fundamental for learning, developing cooperation, trust, and successful collaboration in virtual teams (Hikamah et al, 2021, p. 324; Shrivastava & Prasad, 2020, p. 76; Valente & MacMahon, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that students can utilize instructional films both in the classroom with a teacher and independently, wherever and whenever [18,24]. Furthermore, other studies have indicated that films are capable of enhancing comprehensive thinking and integrating theory with practice [34], as well as increasing one"s interest and understanding in information seeking [35][36][37][38]. However, in previous research, the films did not include stories about contextual material, thus only able to enhance reading motivation, behavior change, and understanding of animation principles.…”
Section: B Discussionmentioning
confidence: 99%
“…materials will allow students to learn and have good communication skills [37]. Therefore, Arabic communication skills materials need to be integrated with local wisdom.…”
mentioning
confidence: 99%